Kinetics Study on the Leaching of Metallic Silver with Ammonium Carbonate as an Eco-Friendly Alternative for Cyanide - Aydogan, Salih; Abdelraheem, Mohamed Taha Osman; Ali, Babiker; Boyrazli, Mustafa (Springer, 2025)
This article describes the dissolution kinetics of metallic silver (Ag) in ammonium carbonate and hydrogen peroxide (H2O2) solution. The influences of temperature, rotation speed, H2O2 concentration, and ammonium carbonate concentration were investigated. The results indicate that ammonium carbonate concentrations between 0.025 and 0.1 M have a significant impact on the dissolution rate. The dissolution rate is positively impacted by H2O2 concentrations between 0.025 M and 0.10 M. Furthermore, there is a positive relationship between the dissolution rate of Ag and the rotation speed. Silver dissolves more readily at temperatures between 20 degrees C and 55 degrees C. However, a temperature > 40 degrees C led to the formation of a silver carbonate layer on the disc when using high concentrations of hydrogen peroxide and ammonium carbonate. The activation energy of 11.10 kJ/mol was calculated, supporting the validity of the Levich equation, which is predicated on the suggestion that mass transfer control describes the extraction rate.
Keywords: Dissolution Behavior; Sodium Thiosulfate; Hydrogen-Peroxide; Gold; Ore; Copper; Thiocyanate; Hydrometallurgy; Recovery; Sulfide